O lugar da teologia é na universidade : a formação de teólogos na Universidade Católica de Pernambuco, desafios e perspectivas - Penteado, Luiz Gonzaga Moura (2014)
This research examined the process of training of theologians at Catholic University of Pernambuco - UNICAP . The analysis started from the Pedagogical Project of Bachelor of Theology ( PPTEO 2013 ) and the evaluation performed with a group of 10 students , establishing possible ways to adapt this proposal to form the current reality . The research is divided into three chapters . The first chapter introduces the significance of theology as a science in the news and recalls the historical process and the discussions on the Recognition and Accreditation of theology courses by the Agency of the Federal Government of Education in Brazil. Although this chapter is reported to walk the historic formation of Catholic theologians in the Archdiocese of Olinda and Recife . The second chapter goes through the epistemological steps of Santos (1997 ) , Morin ( 2000, 2003 , 2005, 2007 ) , Cunha (1998 ) , Vaz (2002 ) and Geffré (2009 ) to a reflection capable of assisting a contemporary reading of scientific knowledge especially with regard to training and theological doing today. The third and final chapter examines the pedagogical project of Bachelor Theology on the University Catholic of Pernambuco and speeches of their students . In conclusion, it is understood that the great challenge of the Bachelor in Theology from University Catholic of Pernambuco is preparing theologians able to take criticism with consistency , dialogical , academic Christian firmness and extreme sensitivity , the great dilemmas in the XXI century.